Effect of Microwave Treatment on Oak Compression Strength - Machado,José Saporiti (2006)
Microwave (electromagnetic) energy is currently used in the treatment of biological damage, in the machine grading of timber and its use for timber drying is foreseen. The exposure of structural timber elements to microwaves, such as for other timber treatments (preservation or fire-retardant), implies analyzing its effect on the mechanical properties of the wood. This paper intends to contribute to this discussion, presenting a preliminary study on the effect of microwave exposure (during 5 and 10min) on compression parallel to grain strength of clear Oak wood. The results obtained show a clear loss of strength due to exposure and to an increase in the time of exposure. Considering the results obtained in this study and by other authors, it becomes clear that more thorough research is needed, bearing in mind the establishment of strength correction factors or rules towards the safe use of this technology for assuring the proper mechanical behaviour of timber.